Bilirubin ditaurate--a sensitive compound for examination of photosensitizers - Jirsa, M; Jirsa, M; Kubát, P (Sbornik lekarsky, 1995)
Bilirubin ditaurate (taurobilirubin) proved to be very suitable for estimation of efficiency of different photosensitizers and for determination of the activity of singlet oxygen. The degree of its bleaching was measured at 450 nm, the excitation light was over 600 nm. Halogen lamps were used as light sources. The decoloration of bilirubin ditaurate was related to the intensity of the light source in the presence of the photosensitizer meso-tetra (4-sulfonatophenyl)-porphine (TPPS4). From photosensitizers conventionally used in photodynamic therapy (photosan 3, TPPS4, and Zn and Al chelates of phthalocyanine) chloroaluminium phthalocyanine was most effective. From synthetic dyes of nonporphyrin type thiazine dyes were most active. The presumption is expressed that the efficiency of noncoherent light is comparable to the laser radiation when photosensitizers with large absorption band 600-700 nm are used for photodynamic therapy.
Keywords: bilirubin; fotosenzibilizující látky; Taurine; fotochemie; Bilirubin; Photochemotherapy; taurin; Photochemistry; fotochemoterapie; Photosensitizing Agents